Analysis of Developing Digital Education Competence Standards for Technical and Vocational Teachers - Widaningsih, L.; Maknun, J.; Dwiyanti, V.; Ramdanisari, A.; Muktiarni, M. (Journal of Technical Education and Training, 2025)
This study aims to formulate digital education competency standards for technical and vocational education and training (TVET) teachers in Indonesia by adapting frameworks from the Australian Qualifications Framework (AQF). As digital transformation accelerates across education sectors, Indonesian TVET teachers must enhance their capabilities to meet the demands of Industry 4.0. A mixed-method approach was employed, involving a quantitative survey of 209 vocational high school teachers across West Java and qualitative focus group discussions (FGDs) with policymakers, practitioners, and digital education experts. The findings indicate that more than 70% of productive subject teachers lack sufficient digital competencies, particularly in integrating information and communication technology (ICT) into classroom practices. Teachers reported low familiarity with digital platforms, e-learning pedagogy, and assessment systems aligned with digital teaching standards. Based on these findings, the study recommends the adoption of AQF-based competency units—such as TAEDEL801, TAEDEL802, and TAELED801—within Indonesia’s National Work Competency Standards (SKKNI). Additionally, a flexible certification pathway is proposed through Recognition of Prior Learning (RPL), allowing teachers to gain certification based on existing experience and skillsets. These recommendations support the development of a nationally recognized and internationally aligned digital competency model. Strengthening teacher digital literacy is essential for preparing students for the digital economy and promoting cross-border professional collaboration within global TVET systems.